2016
DOI: 10.1149/2.0341613jes
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Crystal of NaTCNQ–TCNQ Supported on Different Carbon Materials as Ion-to-Electron Transducer in All-Solid-State Sodium-Selective Electrode

Abstract: This work demonstrates the application of conductive organic crystals (7,7,8,8-tetracyanoquinodimethane (TCNQ) and its sodium salt (NaTCNQ)) supported on carbon nanomaterials (CNMs) as solid contact layer in all-solid-state ion-selective electrodes (ASS-ISEs). As ion-to-electron transductor between the ionically conducting membrane and the electronically conducting glassy carbon new layers based on a high capacity of charge transfer and a redox TCNQ/TCNQ− reaction are proposed. Developed CNM–NaTCNQ–TCNQ-contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…38 Later, the same group used a similar approach by combining carbon nanomaterials with TCNQ and its sodium salt to prepare an ion-to-electron transducer for solid-contact ISEs. 39 The possibility to improve the Na + -SEs sensitivity, linear range, and detection limit, by changing the NaTCNQ/TCNQ ratio was demonstrated in this work. Paczosa-Bator and co-workers also showed that reproducible standard potentials and low detection limits could be achieved for K + -and NO 3 − -SEs using the well-known charge transfer salt TTF-TCNQ as ion-to-electron transducer.…”
Section: Analytical Chemistrymentioning
confidence: 85%
See 1 more Smart Citation
“…38 Later, the same group used a similar approach by combining carbon nanomaterials with TCNQ and its sodium salt to prepare an ion-to-electron transducer for solid-contact ISEs. 39 The possibility to improve the Na + -SEs sensitivity, linear range, and detection limit, by changing the NaTCNQ/TCNQ ratio was demonstrated in this work. Paczosa-Bator and co-workers also showed that reproducible standard potentials and low detection limits could be achieved for K + -and NO 3 − -SEs using the well-known charge transfer salt TTF-TCNQ as ion-to-electron transducer.…”
Section: Analytical Chemistrymentioning
confidence: 85%
“…The improved potential stability and reproducibility of nitrate-selective electrodes were found to relate to the high double layer capacitance of graphene and the presence of the TTF/TTF + redox couple . Later, the same group used a similar approach by combining carbon nanomaterials with TCNQ and its sodium salt to prepare an ion-to-electron transducer for solid-contact ISEs . The possibility to improve the Na + -SEs sensitivity, linear range, and detection limit, by changing the NaTCNQ/TCNQ ratio was demonstrated in this work.…”
Section: Solid-contact Ion-selective Electrodesmentioning
confidence: 97%
“…18 Recently various new SCs have also grown in popularity, such as tetrathiafulvalene (TTF) 19 and 7,7,8,8-tetracyanoquinodimethane (TCNQ) and their radical salts, 20 intercalation compounds (LiFePO 4 /FePO 4 ), 21 Prussian blue analogues, 22 KBr/AgBr, 23 fullerenes, 24 submicron porous carbon spheres, 25 gold nanoparticles, 26,27 molybdenum disulfide, 28 metal–organic frameworks (MOF), 29 and different types of composite materials. 3037…”
mentioning
confidence: 99%
“…solid contacts (SC), have been until now electrically conducting polymers (ECP), different carbon materials with large capacitance, redox couples, , and redox-active compunds . Recently various new SCs have also grown in popularity, such as tetrathiafulvalene (TTF) and 7,7,8,8-tetracyanoquinodimethane (TCNQ) and their radical salts, intercalation compounds (LiFePO 4 /FePO 4 ), Prussian blue analogues, KBr/AgBr, fullerenes, submicron porous carbon spheres, gold nanoparticles, , molybdenum disulfide, metal–organic frameworks (MOF), and different types of composite materials. …”
mentioning
confidence: 99%
“…Various electroactive materials such as conducting polymers [9] and organic conducting crystals [10] which exhibit high redox capacitance, as well as nanomaterials transducers [11] (such as microfibers, microspheres, nanoparticles and microcapsules), nanoporous gold [12] and carbon black [13, 14] characterized by a high double layer capacitance have been already used as internal layers. Metal oxides also appeared to improve electrodes’ properties.…”
mentioning
confidence: 99%